Analysis of needs and teachers' perception towards business teaching materials at SMA Labschool UPI - Hanada Sabilal Khaira; M. Farid Al Hafizh; Pelangi Syaumi Alvina Darmansyah; Hafsah Nugraha; Diemas Arya Komara (Universitas Pendidikan Indonesia, 2023)
This research aims to discuss the importance of understanding teachers' perceptions of business teaching materials to enhance the quality of education. This article seeks to explore the analysis of teachers' needs and perceptions regarding business teaching materials, identify factors influencing their views, and evaluate their impact on the effectiveness of teaching and learning. The research employs a qualitative method with data collection techniques involving interviews and observations. The study results indicate that teachers' perceptions of business teaching materials are influenced by factors such as relevance, practicality, and the attractiveness of the materials. Furthermore, curriculum adjustments and teaching approaches can be implemented to meet the actual needs better, creating a dynamic and relevant learning environment for students. Therefore, this article significantly improves the quality of education at SMA Labschool UPI. Abstrak Penelitian ini bertujuan untuk membahas tentang pentingnya memahami persepsi guru terhadap materi pengajaran bisnis untuk meningkatkan kualitas pembelajaran. Artikel ini bertujuan untuk mengeksplorasi analisis kebutuhan dan persepsi guru terhadap materi pengajaran bisnis, mengidentifikasi faktor-faktor yang memengaruhi pandangan mereka, serta mengevaluasi dampaknya terhadap efektivitas pembelajaran. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan teknik pengumpulan data melalui wawancara dan observasi. Hasil penelitian menunjukkan bahwa persepsi guru terhadap materi pengajaran bisnis dipengaruhi oleh faktor-faktor seperti relevansi, kepraktisan, dan daya tarik materi. Selain itu, penyesuaian kurikulum dan pendekatan pengajaran dapat dilakukan untuk memenuhi kebutuhan sebenarnya, menciptakan lingkungan belajar yang dinamis dan relevan bagi para siswa. Oleh karena itu, artikel ini memberikan kontribusi penting dalam meningkatkan kualitas pembelajaran di SMA Labschool UPI. Kata Kunci: Bisnis; kewirausahaan; materi pengajaran; persepsi guru